Household and occupational air pollution, and demographic drivers of COPD: a hospital-based cross-sectional study in a high-pollution urban setting - Amrendra Kumar Singh; Ashutosh Kumar Pathak; Gaurav Saini (Journal of Environmental Health Science and Engineering, 2026)

Surface modification-driven mitigation of microbiologically influenced corrosion of mild steel by Lantana camara L. extract - Suha Ibrahim; Ashutosh Kumar Pathak; Rudina Ghanem; Y.V. Nancharaiah; Angana Sarkar (International Biodeterioration & Biodegradation, 2026)

The skin lightening properties of mushrooms: A comprehensive review of mechanisms and applications - Reetu; Rahul Jaiswal; Sageer Ahmad; Vijayshwari Mishra; Supriya Pandey; Ashutosh Kumar Yadav; Asad Ali; Rupali Jaiswal; Reema Yadav; Rabiya Ahsan; Tapasya Dwivedi; Sonali; et al. (Next Research, 2026)

Overlooked Health Risks in Rural Settings: PM2.5 Exposure and Concomitant Premature Mortality and Economic Burden Assessment in Punjab and Haryana, India - Amrendra Kumar Singh; Ashutosh Kumar Pathak; Gaurav Saini (Water, Air, & Soil Pollution, 2026)

Hydrogen peroxide is a central ROS regulator in plant immunity - Archana Pathak; Ashutosh Kumar; Aakanksha Wany (Physiology and Molecular Biology of Plants, 2025)

Role of nitrate transporters in plant defense - Janvi Vashi; Archana Pathak; Aakanksha Wany; Ashutosh Kumar (Physiological and Molecular Plant Pathology, 2025)

Steroidal glycoside-rich extract of fenugreek seeds mitigates obesity-induced insulin resistance via attenuation of low-grade inflammation - Sumati Sen; Ashutosh K. Tiwari; Monika Binwal; Monazza Israr; Anant Kumar; Nandini Pathak; Kaveri R. Washimkar; CH Ratnasekhar; Madhav Nilakanth Mugale; Arvind S. Negi; Dnyaneshwar U. Bawankule (Food Research International, 2025)

Development of different regenerative modes for efficient propagation and phytochemical analysis in Tylophora indica (Burm. F.) Merrill: an important medicinal plant - Swati R. Patel; Ashutosh Pathak; Aruna Joshi; Neeta Shrivastava; Sonal Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Enhanced production of pharmaceutically important metabolites using nanoelicitors treatment in callus cultures of Tagetes erecta L. variety sweet orange - Neelam Meena; Ashutosh Pathak; Shamshadul Haq; Sumita Kachhwaha (Natural Product Research, 2025)

Physiological and biochemical responses of Dalbergia sissoo to environmental stressors: Implications for tree mortality and health - Amit Singh Rana; Himanshu Pathak; A.K. Verma; Ashutosh Dubey (Biocatalysis and Agricultural Biotechnology, 2025)

Enhancing agronomic traits of finger millet (Eleusine coracana (L.) gaertn) through seed nano-priming using silicon dioxide nanoparticles (SiO2NPs) - Priya Dudi; Lalita Verma; Ashutosh Pathak; Shamshadul Haq; Sumita Kachhwaha (Journal of Stored Products Research, 2025)

Illigera Grandiflora W.W. Sm. & Jeffrey (Hernandiaceae): a potent source of antioxidants and in silico molecular docking analysis as vascular endothelial growth factor (VEGF) pathway regulator - Ashutosh Pathak; Rahul Das; Deepu Vijayan; Nripemo Odyuo; David Lalsama Baite; Ashiho Asosii Mao (Vegetos, 2025)

DNA barcoding of Spiraea hypericifolia L. and development of an efficient micropropagation using nodal explant: an economically important ornamental and medicinal shrub of Eurasian areal - Vitaliy Kirillov; Ashutosh Pathak; Swati R. Patel; Meirzhan Daulenova; Damira Dyussembekova; Tamara Stikhareva; Ardak Sapiyeva; Aidana Nurtaza; Zhanargul Zhanybekova; Almagul Kakimzhanova (In Vitro Cellular & Developmental Biology - Plant, 2025)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Premature mortality risk and associated economic loss assessment due to PM2.5 exposure in Delhi, India during 2015–2019 - Amrendra Kumar Singh; Ashutosh Kumar Pathak; Gaurav Saini (Air Quality, Atmosphere & Health, 2024)

HPLC and GC/MS analysis of Prunus ulmifolia Franch. (syn. Aflatunia ulmifolia (Franch.) Vassilcz.) leaves growing in South-Eastern Kazakhstan - Vitaliy Kirillov; Ashutosh Pathak; Mussa Zholdasbayev; Gayane Atazhanova; Ardak Sapiyeva; Tamara Stikhareva; Mariya Serafimovich; Meirzhan Daulenova (Natural Product Research, 2024)

An efficient micropropagation protocol for an endangered tree species Aflatunia ulmifolia (Franch.) Vassilcz - Vitaliy Kirillov; Ashutosh Pathak; Swati R. Patel; Mariya Serafimovich; Meirzhan Daulenova; Mikhail Gorbachenkov; Mussa Zholdasbayev; Tamara Stikhareva (In Vitro Cellular & Developmental Biology - Plant, 2024)

Elicitor mediated enhancement of shoot biomass and lupeol production in Hemidesmus indicus (L.) R. Br. ex. Schult. and Tylophora indica (Burm. F.) Merrill using yeast extract and salicylic acid - Ashutosh R. Pathak; Swati R. Patel; Aruna G. Joshi; Neeta Shrivastava; Gaurang Sindhav; Sonal Sharma; Hafsa Ansari (Natural Product Research, 2023)

Micropropagation of Cotoneaster melanocarpus Fisch. ex A.Blytt: an economically important ornamental plant - Vitaliy Kirillov; Ashutosh Pathak; Swati R. Patel; Meirzhan Daulenova; Damira Dyussembekova; Tamara Stikhareva; Alimzhan Rakhimzhanov; Almagul Kakimzhanova (In Vitro Cellular & Developmental Biology - Plant, 2023)

Pollution and similarity status of phytoplankton assemblages as an implied indicator for lake and river health - Nitasha Khatri; Pooja Pathak; Niharika Parmar; Ashutosh Kumar Jha (Sustainable Water Resources Management, 2022)

Sugar Beet Cultivation in India: Prospects for Bio-Ethanol Production and Value-Added Co-Products - Ashutosh Kumar Mall; Varucha Misra; Santeshwari; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2021)

Somatic embryogenesis in Leptadenia reticulata (Retz.) Wight and Arn along with assessment of shoot and callus cultures for HPTLC fingerprint and quantification of p-coumaric acid - Swati R. Patel; Aruna G. Joshi; Ashutosh R. Pathak; Neeta Shrivastava; Sonal Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Chemical Profiling of Tylophora indica (Burm. F.) Merrill. Shoot Cultures Established Through Leaf Explant - Swati R. Patel; Ashutosh R. Pathak; Aruna G. Joshi; Neeta Shrivastava; Sonal Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

3′O-Methyltransferase, Ps3′OMT, from opium poppy: involvement in papaverine biosynthesis - Parul Agarwal; Sumya Pathak; Ravi Shankar Kumar; Yogeshwar Vikram Dhar; Ashutosh Pandey; Sudhir Shukla; Prabodh Kumar Trivedi (Plant Cell Reports, 2019)

In Vitro Antibacterial Activity of Ethno Medicinally Used Lichens Against Three Wound Infecting Genera of Enterobacteriaceae - Ashutosh Pathak; Shashi Kant Shukla; Anand Pandey; Rohit K. Mishra; Rajesh Kumar; Anupam Dikshit (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Infections do not predict shedding in co‐infections with two helminths from a natural system - Isabella M. Cattadori; Benjamin R. Wagner; Laura A. Wodzinski; Ashutosh K. Pathak; Adam Poole; Brian Boag (Ecology, 2014)
Given the health and economic burden associated with the widespread occurrence of co‐infections in humans and agricultural animals, understanding how co‐infections contribute to host heterogeneity to infection and transmission is critical if we are to assess risk of infection based on host characteristics. Here, we examine whether host heterogeneity to infection leads to similar heterogeneity in transmission in a population of rabbits single and co‐infected with two helminths and monitored monthly for eight years. Compared to single infections, co‐infected rabbits carried higher Trichostrongylus retortaeformis intensities, shorter worms with fewer eggs in utero, and shed similar numbers of parasite eggs. In contrast, the same co‐infected rabbits harbored fewer Graphidium strigosum with longer bodies and more eggs in utero, and shed more eggs of this helminth. A positive density‐dependent relationship between fecundity and intensity was found for T. retortaeformis but not G. strigosum in co‐infected rabbits. Juvenile rabbits contributed to most of the infection and shedding of T. retortaeformis , while adult hosts were more important for G. strigosum dynamics of infection and transmission, and this pattern was consistent in single and co‐infected individuals. This host–parasite system suggests that we cannot predict the pattern of parasite shedding during co‐infections based on intensity of infection alone. We suggest that a mismatching between susceptibility and infectiousness should be expected in helminth co‐infections and should not be overlooked.

Molecular characterization of plant growth promoting rhizobacteria that enhance peroxidase and phenylalanine ammonia-lyase activities in chile (Capsicum annuum L.) and tomato (Lycopersicon esculentum Mill.) - Alok Sharma; Ashutosh Pathak; Manvika Sahgal; Jean-Marie Meyer; Victor Wray; Bhavdish N. Johri (Archives of Microbiology, 2007)